KAJIAN PENGATURAN PERSONEL AVIOBRIDE GUNA MENINGKATKAN PELAYANAN DI BANDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Ni Putu Hita Widiandari; Ubaedillah; Nunuk Praptiningsih, Nunuk (Jurnal Teknologi Kedirgantaraan, 2025)
This study aims to analyze the personnel deployment of aviobridge operators at I Gusti Ngurah Rai International Airport to improve airside operational efficiency. Using a descriptive qualitative approach, data were gathered through direct observation, structured interviews with AMC officers, aviobridge operators, ground handling personnel, and supported by document review. The study found that the current shift composition of 12–13 personnel is below the operational standard of 18 per shift for 33 aviobridges, causing service delays, multitasking, and coordination issues. The shortage impacts docking/undocking timeliness, leading to warnings and reduced service quality. The study highlights the need for zone-based task distribution, additional personnel gathering points, better inter-unit coordination, and pre-operation readiness. Unlike previous studies, this research emphasizes internal workforce structuring and adaptive shift planning. These findings are particularly relevant for high-traffic airports and may inform broader airport staffing strategies across similar environments. Improvements in scheduling and task zoning are recommended to enhance personnel responsiveness, reduce delays, and support punctual flight operations.